Walter Benjamin and history - Benjamin, Andrew E., 1952-; ebrary, Inc. (London : Continuum, 2005)
Walter Benjamin's collection of fragments, Theses on the Philosophy of History, play a determining role in how his thought is understood, as well as in the debate about the interplay between politics, history and time. Walter Benjamin and History is the first volume to give access to the themes and problems raised by the Theses, providing valuable exegetical and historical work on the text. The essays collected here are all the work of noted Benjamin scholars, and pursue the themes central to the Theses.
Introduction / Andrew Benjamin -- The supposition of the aura: the now, the then, and modernity / Georges Didi-Huberman -- The shortness of history, or photography In Nuce: Benjamin's attenuation of the negative / David Ferris -- 'Now': Walter Benjamin on historical time / Werner Hamacher -- Down the K. hole: Walter Benjamin's destructive land-surveying of history / Stephanie Polsky -- The sickness of tradition: between melancholia and fetishism / Rebecca Comay -- Trembling contours: Kierkegaard-Benjamin-Brecht / Rainer Nägele -- The subject of history: the temporality of parataxis in Benjamin's historiography / Dimitris Vardoulakis -- Tradition as injunction: Benjamin and the critique of historicisms / Philippe Simay -- Boredom and distraction: the moods of modernity / Andrew Benjamin -- Walter Benjamin's interior history / Charles Rice -- What is the matter with architectural history? / Gevork Hartoonian -- Messianic epistemology: Thesis XV / Robert Gibbs -- Non-messianic political theology in Benjamin's 'On the concept of history' / Howard Caygill
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Benjamin, Walter, -- 1892-1940; 20. století; německá filozofie -- 20. století; filozofie dějin -- Německo -- 20. století; German philosophy -- 20th century; philosophy of history -- Germany -- 20th century; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online